Implementasi Algoritma Base64 Pada Sistem Antrian Pasien Berbasis Website (Studi Kasus Puskesmas Bangunsari Kec.Dolopo Kab.Madiun - Istiyani, Khairul; Nurfitri, Khoiru; Astuti, Indah Puji (Telematika, 2024)
Bangunsari Health Center in providing services implements various stages of the process that must be passed. Among them is the registration process, where many patients often do not get a queue number because there are restrictions in certain poles every day. In the registration process, patients must submit identities such as Name, NIK, Date of birth, address and telephone number. This data is sensitive information that must be kept confidential, especially since the data is increasing every day. Therefore, to overcome these problems, namely through the development of a website-based patient queuing system by applying an encryption algorithm. With the aim that it will be useful to simplify the queuing process and secure the private data to avoid misuse and data leakage, by going through the data encryption or cryptography process. Cryptography is the science and art of maintaining the confidentiality of messages by encoding them into a form that is no longer understandable in meaning. Data encryption has several algorithms that can be used, one of which is the Base64 algorithm, the Base64 algorithm can be useful in encoding binary data so that it turns into a format that can be printed normally into ASCII format based on the number 64. To ensure that the website-based patient queuing system runs according to the flow that has been made, it is tested using the black box method with the results of the entire system functioning and running according to the source code that has been designed. Meanwhile, the results of implementing base64 run according to the rules that have been tested using the whitebox method and the base64 decode web site, with the results of whitebox and base64 site testing, it is known that the data results are encrypted in the database. So that if there are intruders who enter the database, they cannot read the data that has been encrypted in the form of random text in it.